Legal Protection Fulfillment of the Rights of Child Victims of Sexual Violence - Inayatul Khaqu Al-Amini; Yusuf Saefudin (Proceedings Series on Social Sciences & Humanities, 2023)
Children are part of the younger generation as one of the human resources who are the potential and successors of the nation's struggle ideals. Based on data from the Ministry of PPPA, there were also 8,478 cases of violence against women in 2021, of which 15 percent or 1,272 cases were cases of sexual violence. The problem of sexual violence in children is very concerning because of the tremendous negative impact experienced by children after the incident even after many years of the incident have passed. The recovery of child victims of sexual crimes is a complex issue in the psychological recovery of child victims. But unfortunately, the law in Indonesia is still only focused on how to provide punishment for perpetrators, but has not paid attention to how the physical and psychological condition of the victim. Therefore, it is necessary to formulate preventive (preventive) and curative (healing) measures carried out by all parties to be able to fulfill the rights of victims, especially physical and psychological trauma assistance. The purpose of this study is to determine how preventive and curative steps to assist physical and psychological trauma as a form of fulfilling the rights of child victims of sexual violence. The research method used is normative juridical, which is a type of legal research that uses research materials in the form of theories, concepts, legal principles, and legal regulations that concern the subject of research or in other words normative juridical research is research that uses sources from literature or secondary data. The results of this study are how preventive and curative efforts to assist physical and psychological trauma as a form of fulfilling the rights of children victims of sexual violence are appropriate and who can contribute to these efforts.